1995
DOI: 10.1093/rheumatology/34.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sarcoid Arthritis: Occurrence, Seasonal Onset, Clinical Features and Outcome

Abstract: In a 2-yr prospective follow-up study of patients presenting clinically with possible reactive arthritis (ReA), 17 (9%) of the patients turned out to have acute sarcoid arthritis (SA). The number of new cases of SA per year was 2.9/100,000 persons in the city of Oslo between 18 and 60 yr of age. The onset of SA clustered in the spring. All the SA patients presented with bilateral ankle joint involvement and bilateral hilar lymphadenopathy, and ten (59%) presented with the triad of erythema nodosum, arthritis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
7

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 0 publications
3
52
1
7
Order By: Relevance
“…A cluster of sarcoid arthritis in the spring, of which 10 out of 17 cases also had EN and lung involvement, was reported from Norway [1]. Unlike the present study there was no female preponderance but most had stage I chest radiography.…”
Section: Discussioncontrasting
confidence: 67%
“…A cluster of sarcoid arthritis in the spring, of which 10 out of 17 cases also had EN and lung involvement, was reported from Norway [1]. Unlike the present study there was no female preponderance but most had stage I chest radiography.…”
Section: Discussioncontrasting
confidence: 67%
“…Results demonstrated that despite early treatment and an overall initial improvement, the majority of patients were still symptomatic at 12 months. This finding indicates a significant level of disease persistence in a young population of patients and is consistent with other published studies (2,3,7). The purpose of the current study was to assess the efficacy of early intervention with intraarticular corticosteroids followed by therapy with SSZ in patients with persistent disease compared with initial NSAID therapy alone followed by later intervention with intraarticular corticosteroid and SSZ in cases of disease persistence.…”
Section: Introductionsupporting
confidence: 88%
“…The similar clustering for the two patient subgroups is also in line with the suggestion that EN-positive and EN-negative patients have different manifestations of the same disease, with the same etiology. Several previous studies on acute sarcoidosis with EN, as well as on acute sarcoid arthritis, reported a seasonal clustering to the spring months (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 89%